The economic burden of diabetes for patients and their families in Ecuador - Coello Gómez, Gladys (2018)
Diabetes mellitus type II, is the main cause of death in Ecuador and in general, worldwide, is a concern for governments because of the economic impact of the disease on the family budget and the state budget. The prevalence of the disease has increased without the existence of proven public policy mechanisms that could slow down its progress. The present research seeks to contribute with guiding elements, economic and quantifiable, that serve as the basis for the design of public programs tending to pay greater attention to public investment in prevention, since once the disease is contracted, the economic burden of diabetes for patients, their families and the State it borders 60% of the unified monthly basic salary; cost that generates that patients maintain incomplete treatments with consequences such as more serious and expensive health problems, premature death, low productivity, among others. DOI: https://doi.org/10.31164/bcoyu.19.2018.679 URL: http://revistas.uta.edu.ec/erevista/index.php/bcoyu/article/view/679